HUBUNGAN USIA DAN JARAK KEHAMILAN DENGAN KEJADIAN ANEMIA KLINIS SELAMA KEHAMILAN - Vevi Gusnidarsih (Jurnal Asuhan Ibu dan Anak, 2020)
ABSTRACT Pregnancy anemia called "potential denger to mother and child" (potentially harmful to mothers and children), because that is anemia requires serious attention from all related parties in health care. Data from the World Health Organizazion (WHO), globally the prevalence of anemia in pregnant women around the world was 41.8%, in 2018 increased to 48.9% (Rikesdas, 2018). One cause of occurrence and clinical anemia during pregnancy is the age and distance of pregnancy. The research methodology used in this study is an analytical survey using cross sectional methods. The population of this study includes all expectant mothers who are in the working area of Talang Randai public health center in south Bengkulu period of February-March 2018 amounted to 58 people. Data is analyzed using Chi-square. The results of the study obtained 53.4% of the respondents had anemia, 41.4% of the respondents with age at risk is < 20 and > 35 year, 37.5% of respondents with pregnancy distance at risk is < 2 years. The Chi-Square statistical shows the Î± value of < 0.005 meaning there is a meaningful relationship between the ages (P = 0,002) and the gestational distance (P = 0,003) with the incidence of clinical anemia during pregnancy in the working area of Talang Randai public health center in South Bengkulu Regency. Keywords: Anemia, age, pregnancy distance